PERANCANGAN ULANG TATA LETAK FASILITAS PRODUKSI DENGAN METODE GRAFIK DAN METODE CRAFT DI UD. PRIMADONA - nita kuswardhani; Bertung Suryadharma (AGROINTEK, 2021)
UD. Primadona is a company that sells typical Jember snacks. At the moment, the condition of the facility layout of UD. Primadona faced many problems. One of them is a distinctive design that there is a long flow of material transfer. Transferring materials from the cutting department to the packaging department must go through the production department passed (backtrack). This flow can lead to a big total displacement moment, allowing an increase in material handling costs and indirectly increasing production costs. So, it is necessary to make or change the layout to be more effective and efficient. This study aimed to design using two methods, the CRAFT method and the Graph method. The results showed that alternative graphic method 2 was the best solution based on Material Handling Cost (OMH). This method has less displacement moment per day, and total OMH than the existing design, 89 meters per day and Rp. 7,039.90 respectively.